Effect of Temperature on Reproduction and Sex Ratio of Guppy (Poecilia reticulata Peters) - H. Arfah; S. Mariam; . Alimuddin (Jurnal Akuakultur Indonesia)
Water temperature could affect the reproduction of broodstock and sex ratio of progeny.  In this study, broodstock of guppy (Poecilia reticulata Peters) was reared in different temperature to determine its effect on reproduction of broodstock and sex ratio of their progeny. The result of study show that broodstock reared at 27°C produced more fry (16 males mean) than that of 30°C (10 males), while broodstock reared at 33°C produced no progeny.  Percentage of male fish produced by broodstock reared at 30°C is higher than that of 27°C.  Incubation time of embryo before birth is sorter in broodstock reared at 30°C (4-12 days) compared with 27°C (18-22 days).  However, several progeny of broodstock reared at 30°C had abnormal vertebrae.